Studying the Effect of Stiffener Configurations on the Structural Response of Hopper Wagon Using Finite Element Analysis - Rafif Ibnu Ardiansyah; Achmad Fauzan Hery Soegiharto; Mohamad Irkham Mamungkas; Abi Mufid Octavio (Advances in Technology Innovation, 2026)
Hopper wagons are subjected to complex loading conditions during granular material transportation. This study aims to evaluate the effect of stiffener configurations on the structural response of a hopper wagon using finite-element analysis under multi-compartment loading conditions. Three configurations are analyzed: vertical, rectangular, and triangulated stiffeners, with a non-uniform distribution of granular material to reflect real-world operating conditions. The results show that the triangulated configuration exhibits the lowest average deformation (15.466 mm) and a more uniform stress distribution. The vertical configuration yields the lowest maximum stress and the highest safety factor, but is less effective at controlling global deformation. Conversely, the rectangular configuration increases structural stiffness but produces stresses close to the material’s yield limit. The analysis also indicates that the most critical loading conditions do not always occur under full loading. Overall, the triangulated configuration provides the best balance among stiffness, stability, and structural safety across various loading conditions.